A study of thermal behaviour during submerged arc welding - Ghosh, Aniruddha (Strojniški vestnik, 2013)
The present study reports on thermal behavior during submerged arc welding considering an oval shaped heat source. The welding process is represented by the energy conservation equation where the moving electrode is incorporated considering an oval shaped Gaussian heat source. The governing equation is solved based on the Green function solution and subsequently considered the effect of heat in the weld pool and convection after welding. The prediction agrees well with the experiments and it was found that an oval shape is a better approximation for the heat source.
Keywords: convective heat loss; Gaussov vir toplote ovalne oblike; konvektivne toplotne izgube; lumped system; obločno varjenje pod praškom; oval shape Gaussian heat source; parabolic weld pool; parabolična talilna kopel; skopljeni sistem; submerged arc welding